Patrons of Greg's Ballroom - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows portrait of four patrons of Greg's Ballroom on the bar's one year anniversary. Left-to-right are Alex, Christopher, Wayne and Lester.